2020
DOI: 10.1159/000504244
|View full text |Cite
|
Sign up to set email alerts
|

Immunoadsorption for Recurrent Primary Focal Segmental Glomerulosclerosis on Kidney Allografts: A Single-Center Experience and Literature Review

Abstract: Introduction: Primary focal and segmental glomerulosclerosis (FSGS) frequently reoccurs on kidney transplants and may lead to premature allograft loss. There are no guidelines for treating FSGS recurrence on allografts; treatment is based on apheresis (plasma exchange plasmapheresis [PP], semi-specific immunoadsorption [IA] with reusable columns) plus rituximab. Objective: We aimed to assess the efficacy of IA to treat recurrent FSGS. Methods: We report on 7 patients with recurrent FSGS on kidney allograft (pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Furthermore, since 2000, rituximab has been widely used in FSGS recurrence as adjuvant to plasmapheresis. Rituximab depletes B lymphocytes and also enhances regulatory T cell activity; T cell malfunction is believed to play a major role in pathogenesis of proteinuria [17,41,42]. Moreover, there is evidence of non-immunological actions since rituximab directly modulates podocyte function by preventing the disruption and remodeling of actin cytoskeleton [42].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, since 2000, rituximab has been widely used in FSGS recurrence as adjuvant to plasmapheresis. Rituximab depletes B lymphocytes and also enhances regulatory T cell activity; T cell malfunction is believed to play a major role in pathogenesis of proteinuria [17,41,42]. Moreover, there is evidence of non-immunological actions since rituximab directly modulates podocyte function by preventing the disruption and remodeling of actin cytoskeleton [42].…”
Section: Discussionmentioning
confidence: 99%
“…Rituximab depletes B lymphocytes and also enhances regulatory T cell activity; T cell malfunction is believed to play a major role in pathogenesis of proteinuria [17,41,42]. Moreover, there is evidence of non-immunological actions since rituximab directly modulates podocyte function by preventing the disruption and remodeling of actin cytoskeleton [42]. An overall response rate of 58 to 79% with the use of rituximab has been reported in such patients [22,[41][42][43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This factor has been suggested by several observations, including the development of proteinuria in rats after injection of proteins eluted from an immunoadsorption (IA) column used by FSGS-treated patients [ 27 ]. This was also suggested by: (i) the disappearance of nephrotic syndrome after transplantation of a kidney from an FSGS patient into a non-FSGS kidney recipient [ 7 , 28 , 29 ]; (ii) the occurrence of a nephrotic syndrome in a newborn of an FSGS mother [ 30 ]; and (iii) the control of nephrotic syndrome with apheresis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Limited studies, mainly case reports or case series, have explored the use of immunoadsorption (IA) to treat children with recurrent FSGS after KTx [13, 14]. Among them, a recent French cohort study in pediatric patients reported the efficacy of IA in the management of recurrent FSGS after KTx [9].…”
Section: Introductionmentioning
confidence: 99%